Dichlorodioxomolybdenum(VI) complexes bearing oxygen-donor ligands as olefin epoxidation catalysts - Oliveira, Tânia S. M. (2015)
Treatment of the solvent adduct [MoO2Cl2(THF)2] with either 2 equivalents of N,N-dimethylbenzamide (DMB) or 1 equivalent of N,N'-diethyloxamide (DEO) gave the dioxomolybdenum(vi) complexes [MoO2Cl2(DMB)2] () and [MoO2Cl2(DEO)] (). The molecular structures of and were determined by single-crystal X-ray diffraction. Both complexes present a distorted octahedral geometry and adopt the cis-oxo, trans-Cl, cis-L configuration typical of complexes of the type [MoO2X2(L)n], with either the monodentate DMB or bidentate DEO oxygen-donor ligands occupying the equatorial positions trans to the oxo groups. The complexes were applied as homogeneous catalysts for the epoxidation of olefins, namely cis-cyclooctene (Cy), 1-octene, trans-2-octene, α-pinene and (R)-(+)-limonene, using tert-butylhydroperoxide (TBHP) as oxidant. In the epoxidation of Cy at 55 °C, the desired epoxide was the only product and turnover frequencies in the range of ca. 3150-3200 mol molMo(-1) h(-1) could be reached. The catalytic production of cyclooctene oxide was investigated in detail, varying either the reaction temperature or the cosolvent. Complexes and were also applied in liquid-liquid biphasic catalytic epoxidation reactions by using an ionic liquid of the type [C4mim][X] (C4mim = 1-n-butyl-3-methylimidazolium; X = NTf2, BF4 or PF6] as a solvent to immobilise the metal catalysts. Recycling for multiple catalytic runs was achieved without loss of activity.